Effect of Growth Stages on Anthocyanins and Polyphenols in the Root System of Sweet Potato - Yuno Setoguchi; Soya Nakagawa; Ryo Ohmura; Saki Toshima; Hyungjun Park; Yosuke Narasako; Tomonari Hirano; Motoyasu Otani; Hisato Kunitake (Plants, 2023)
The storage roots of purple-fleshed sweet potato contain a variety of anthocyanins and polyphenols. Little is known about changes in the total content and composition of anthocyanins and polyphenols in the early growth stages of the root system. In this study, we investigated the changes in anthocyanins and polyphenols in the root system of purple-fleshed sweet potato cultivars at 15, 30, 45, and 60 days after transplant (DAT). Unexpectedly, the highest percentage of acylated anthocyanins in three purple-fleshed cultivars among all growth stages was at 15 DAT. On the other hand, the total polyphenol content in the early growth stages of the root system increased rapidly toward 45 DAT, just before the beginning of storage root enlargement, and then decreased rapidly as the storage roots began to enlarge. These data indicate that the early growth stage of the root system is a critical time. This timing may present a strategy to maximize the accumulation of polyphenols with high antioxidant activity, as well as acylated anthocyanins, to protect against abiotic and biotic stresses.